Corn and Soybean Production – 2023 Summary - Gretchen F. Sassenrath; Jane Lingenfelser; Xiaomao Lin (Kansas Agricultural Experiment Station Research Reports, 2024)
Soybean and corn varieties were tested in replicated field trials at the Southeast Research and Extension Center in Parsons through the Kansas State University variety testing program. In total, 21 corn varieties and full-, mid-, and short-season maturity checks were tested. Fifteen full-season and nine double-cropped soybean varieties were tested, with three maturity checks ranging in maturity from 3.1 to 5.2. Fourteen sunflower varieties were also tested. The 2023 summer crop growing season was nearly average for both temperature and rainfall. Yields from the variety tests were slightly lower than the 13-year average.
Keywords: crop variety testing; double cropped soybeans; rainfall; growing degree days; extreme degree days